Ex vivo Retrieval of Mature Oocytes for Fertility Preservation in a Patient with Bilateral Borderline Ovarian Tumor - Bruno Ramalho de Carvalho; Geórgia Fontes Cintra; Taise Moura Franceschi; Íris de Oliveira Cabral; Leandro Santos de Araújo Resende; Brenda Pires Gumz; Thiago David Alves Pinto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract We report a case of ultrasound-guided ex vivo oocyte retrieval for fertility preservation in a woman with bilateral borderline ovarian tumor, for whom conventional transvaginal oocyte retrieval was deemed unsafe because of the increased risk of malignant cell spillage. Ovarian stimulation with gonadotropins was performed. Surgery was scheduled according to the ovarian response to exogenous gonadotropic stimulation; oophorectomized specimens were obtained by laparoscopy, and oocyte retrieval was performed ~ 37 hours after the ovulatory trigger. The sum of 20 ovarian follicles were aspirated, and 16 oocytes were obtained.We performed vitrification of 12 metaphase II oocytes and 3 oocytes matured in vitro. Our result emphasizes the viability of ex vivo mature oocyte retrieval after controlled ovarian stimulation for those with high risk of malignant dissemination by conventional approach.